2021
DOI: 10.1093/braincomms/fcab147
|View full text |Cite
|
Sign up to set email alerts
|

Soluble amyloid beta-containing aggregates are present throughout the brain at early stages of Alzheimer’s disease

Abstract: Protein aggregation likely plays a key role in the initiation and spreading of Alzheimer’s disease pathology through the brain. Soluble aggregates of amyloid beta are believed to play a key role in this process. However, the aggregates present in humans are still poorly characterised due to a lack of suitable methods required for characterising the low concentration of heterogeneous aggregates present. We have used a variety of biophysical methods to characterise the aggregates present in human Alzheimer’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…aggregates from controls, which are larger on average, would be less inflammatory. This result is similar to the result of our recent study on a Braak stage III AD brains, where we found that the hippocampus contained a higher proportion of smaller aggregates than the visual association cortex and that these hippocampal aggregates caused an increased inflammatory response 59 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…aggregates from controls, which are larger on average, would be less inflammatory. This result is similar to the result of our recent study on a Braak stage III AD brains, where we found that the hippocampus contained a higher proportion of smaller aggregates than the visual association cortex and that these hippocampal aggregates caused an increased inflammatory response 59 .…”
Section: Discussionsupporting
confidence: 92%
“…Coverslip preparation was done as described previously 59,62,63 . Afterwards the coverslip was passivated with neutravidin (0.2 mg/mL) diluted in 0.05% PBS-T(v/v) (tween20 Cat.…”
Section: Single-molecule Super-resolution Imagingmentioning
confidence: 99%
“…Here, we circumvent these multiple drawbacks by using a human microglia xenotransplantation model 22,23 . We provide a full map of the different cell states adopted by human microglia in response to amyloid-b pathology, including the elusive component of soluble oligomeric amyloid-β that have been linked to neuroinflammation, neurodegeneration and cognitive impairment [24][25][26][27] . We show that human microglia react very differently from mouse microglia to amyloid-b pathology.…”
mentioning
confidence: 99%
“…The aggregates of Aβ can be of different size and solubility, ranging from small soluble dimers and trimers to the intermediate soluble species (termed as oligomers and protofibrils) and to finally insoluble fibrils, which constitute the core components of the amyloid-plaques [1][2][3]. Different Aβ aggregates exhibit distinct toxicity mechanisms, with a growing body of evidence suggesting a correlation of oligomers and protofibrils with the neuronal and synaptic damage observed in AD [4][5][6]. Due to their small size and high mobility, soluble oligomers of Aβ are more likely to exert their neurotoxic effects through their ability to permeabilize and cross cell membranes [7,8], while the slightly larger protofibrils have been shown to induce toxicity by other mechanisms, for example, by enhancing neuroinflammation [7].…”
Section: Introductionmentioning
confidence: 99%